Epicardial adipose tissue and cardiovascular diseases. (1st March 2019) - Ansaldo, Anna Maria; Montecucco, Fabrizio; Sahebkar, Amirhossein; Dallegri, Franco; Carbone, Federico
Abstract: Obesity is a heterogeneous disease with different degrees of cardiovascular (CV) and metabolic manifestations. Certain ectopic fat depots may contribute to obesity-related CV risk and may explain part of the risk differential observed in metabolically healthy obese and the so called "obesity paradox". The growing interest towards the potential impact of epicardial adipose tissue (EAT) in cardiovascular (CV) risk has led to deepen its biological function. Genetic, epigenetic and environmental factors may drive the shift towards a dysfunctional EAT characterized by a pro-inflammatory and pro-fibrotic phenotype. Due to the close anatomic proximity to coronary arteries, a thicker and dysfunctional EAT actively contribute to development and progression of coronary atherosclerosis. Beside classical paracrine transmission, EAT may directly release mediators into the vasa vasorum of the coronary arterial wall, a mechanism referred to as "vasocrine". Similarly, the pro-inflammatory and pro-fibrotic secretome characterizing dysfunctional EAT may impair cardiac structure and function, thus being implicated in the pathogenesis of diastolic heart failure and atrial fibrillation. The development of 3D imaging techniques have paved the way for clarifying the causative role of EAT in CV pathophysiology, the use of EAT volume/thickness in CV risk stratification and potential cardio-protective effects of EAT reduction. The aim of this narrative review is to update current knowledge on the pathophysiological functions of EAT, focusing on basic mechanisms and potential clinical implications. Graphical abstract: Highlights: Obesity is a heterogeneous disease with different cardiovascular risk. Different factors are responsible for dysfunctional epicardial adipose tissue. Dysfunctional epicardial adipose tissue impairs cardiac structure/function.